TUGAS DAN FUNGSI KANTOR KEMENTERIAN AGAMA KABUPATEN BANGGAI DALAM PEMBIMBINGAN MANASIK HAJI - Pawata, Ru'yan; Daeng Maroa, Mustating; Sucipto, Dri (Jurnal Yustisiabel, 2025)
This study aims to analyze the implementation of the duties and functions of the Banggai Regency Ministry of Religious Affairs Office in guiding hajj rituals and the factors that influence them. This study uses an empirical legal method with primary and secondary data. Hajj ritual guidance is carried out through certain stages, including the delivery of materials related to the hajj, health, and mental and spiritual development. The resource individuals come from employees of the Ministry of Religious Affairs, local governments, and related agencies. Supporting factors for the implementation of hajj rituals include regulations, facilities, family involvement, and cooperation with local governments. However, there are obstacles such as low understanding of participants, physical conditions of the congregation, and transportation and accessibility constraints.